Voices from the Hills: A Study of Ao Literature and Oral Traditions - Ankit Kharb (The Context, 2025)
The rich cultural legacy and changing literary environment of the Ao Naga group in Northeast India are examined in the present paper. To understand how oral narratives have influenced and maintained the community's collective memory and identity, this study examines the relationship between oral traditions—such as folktales, myths, ballads, and proverbs—and modern Ao literature. In addition to examining the shift from oral to written forms resulting from colonial and missionary influences, the study emphasizes the importance of storytelling in preserving indigenous knowledge systems, values, and worldviews. This study emphasizes the adaptability and persistence of Ao cultural manifestations in the face of social and political change by examining both contemporary literary writings published in Ao and English as well as traditional oral performances. Additionally, it considers how language, memory, and performance contribute to the preservation of cultural legacy. The work's ultimate goal is to advance knowledge of Indian tribal literature and the importance of indigenous voices in the larger conversation about literature, identity, and decolonization.